Intraband dynamics of mid-infrared HgTe quantum dots. Issue 11 (7th December 2021) - Ruppert, Matthias; Bui, Hanh; Sagar, Laxmi Kishore; Geiregat, Pieter; Hens, Zeger; Bester, Gabriel; Huse, Nils
Abstract : Femtosecond pump–probe spectroscopy reveals ultrafast carrier dynamics in mid-infrared (MIR) colloidal HgTe nanoparticles with a bandgap of 2.5 μm at a mean energy dissipation rate of 0.36 eV ps −1 irrespective of excitation wavelength. Abstract : Femtosecond pump–probe spectroscopy reveals ultrafast carrier dynamics in mid-infrared (MIR) colloidal HgTe nanoparticles with a bandgap of 2.5 μm. We observe intraband relaxation processes after photoexcitation ranging from resonant excitation up to the multi-exciton generation (MEG) regime by identifying initially excited states from atomic effective pseudopotential calculations. Our study elucidates the earliest dynamics below 10 ps in this technologically relevant material. With increasing photon energy, we find carrier relaxation times as long as 2.1 ps in the MEG regime close to the ionization threshold of the particles. For all photon energies, we extract a constant mean carrier energy dissipation rate of 0.36 eV ps −1 from which we infer negligible impact of the density of states on carrier cooling.